Pengaruh Penerapan Strategi Crossword Puzzle Terhadap Motivasi Belajar Siswa Pada Tema 1 Subtema 1 Siswa Kelas V SD Negeri 060927 Medan T.A 2023/2024 - Nurul Khafizah; Risma Sitohang (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research was carried out to determine the effect of implementing the crossword puzzle strategy on students learning motivation un theme 1 subtheme 1 learning 3 class V SDN 060927 Medan.the population in this study was 54 students consisting of class V students. The sample in the study used was simple random sampling which is a random sampling technique without playing attention to the similaritis in the population. Data was collected using a questionnaire and strenghened using the test questions provided, and the research was carried out using a quasi experimental design. The result obtained in this research show that the applicationof the crossword puzzle strategy has a significant influence on the learning motivation of students at SD 060927 Medan. The average obtained from the postest score in the experimental class and control class shows that the postest score in the experimental class is greater than the postest score in the control class, namely 88,33 > 73,56. Meanwhile, in the research hypothesis, the resulting t count value is greater than t table , namely 14,84 > 2.00. so that the application of the crossword puzzle strategy can have an influence on the learning motivation of students at SDN 060927 Medan.